The Role of Hemoglobin in Maintaining Health: A Literature Review - Agesti, Nireza; Damrah, Damrah; Rasyid, Willadi; Welis, Wilda; Rahman, Dally; Zarya, Fiky (JURNAL INFO KESEHATAN, 2024)
The role of hemoglobin in maintaining health is still not fully understood Thoroughly. Therefore, this literature review aims to uncover comprehensively the role of hemoglobin in maintaining health. Objective: The purpose of this literature review is to investigate the role of hemoglobin in maintaining health by collecting and analyzing current findings in the scientific literature. The methodology used is a systematic search through academic databases such as PubMed, Google Scholar, and Scopus using relevant keywords such as "hemoglobin", "health maintenance", and "literature review". Articles that meet the inclusion criteria are selected for analysis. The samples in this review literature are scientific articles published within a certain time frame and focus on the role of hemoglobin in maintaining health. The population studied includes humans of various age groups and health conditions. The results of the analysis stated that hemoglobin plays an important role in maintaining oxygen balance in the body, supporting the function of vital organs, and preventing diseases related to hemoglobin disorders. Factors such as nutrition, environment, and health conditions can affect a person's hemoglobin levels. In conclusion, this literature review confirms that a deep understanding of hemoglobin's role in maintaining health is important for the development of prevention and management strategies for diseases associated with hemoglobin disorders. Thus, further research in this area is needed to improve general well-being.